Proteins and Peroxidase in Callus and Suspension Cultures of Apple : A Study Using Ultrathin-Layer Isoelectric Focusing, Sensitive Silver Staining of Proteins, and Peroxidase Isozyme Visualization - Berger, Ralf G. (1985)
Different methods for the isolation of soluble proteins were applied to cell cultures of three apple cultivars (Malus sylvestris Mill.), best results being obtained with a rapid technique based on freezing and thawing. Ultrathin-layer isoelectric focusing followed by an improved silver staining method has shown that proteins from apple callus cultures consist of some 60 to 80 zones, with isoelectric points mainly between pH 4 to 7. Depending on protein content, adequate silver staining is achieved with 50 to 500 cells. Protein patterns of callus cultures allowed clear discrimination of cultivars. Protein and peroxidase isozyme patterns in cell saps of suspension cultures show striking differences during the growth cycle, whereas the protein patterns from the nutrient media were constant over the entire cultivation period and closely resembled the patterns of stationary phase and callus cells.